Comparison between standard ligament reconstruction and tendon interposition vs adding an interference screw for flexor carpi radialis fixation. A pilot study - Rocio del Pilar Pasache-Lozano; Edwin Alfonso Valencia-Ramon; Marie-Christine Perron; Kelly Trask; David G. Johnston; J. Andrew I. Trenholm (Journal of Orthopaedic Reports, 2023)
Introduction: The traditional ligament reconstruction and tendon interposition (LRTI) procedure requires a trapeziectomy with the reconstruction of the palmar oblique ligament. Introduction of an interference screw (IS) during the tendon interposition is intended to improve tensioning of the beak ligament reconstruction and limit subsidence which may increase stability for the patient postoperatively. Material and methods: Non-inferiority, clinical, blinded, and randomized trial was performed. Twenty patients were randomized to one of the two treatment groups (Standard LRTI vs LRTI + IS). Four patients did not receive surgery during the allotted time. Finally, 16 patients (8 per group) had completed follow-up data at the end of the designated 2-year follow up. Results: Equivalent functional and radiographic outcomes were found. Trapezial height at 2 years was 4.44 mm for standard LRTI and 3.83 mm for LRTI with screw. At the end of the follow up period both groups had comparable grip strength. Mean improvement of DASH score, VAS and EQ5D was similar in both groups, showing good outcomes for both procedures. Conclusion: Ligament reconstruction and tendon interposition with and without interference screw has shown equivalent results in a 2-year follow-up related to stability and functional outcomes. Interference screw is a safe and reliable technique with no difference in pain or complication rates. Level of evidence: Therapeutic II.